Gastroprotective effect of ethylacetate fraction of the leaves of Hannoa klaineana on aspirin and histamine-induced gastric ulcer in rats - Abubakar, Ibrahim; Muhammad Yankuzo, Hassan; Shuaibu Baraya, Yusha'u; Abubakar Gusau, Mu'azu (International Journal of Pharmacology and Toxicology, 2020)
Background: Peptic ulcer disease remains endemic in our society affecting about four million people every year worldwide. Hannoa klaineana is used traditionally in the treatment of various gastrointestinal diseases including ulcer. Aim: This study aims at evaluating the gastroprotective effect of ethylacetate fraction of the leaves of Hannoa klaineana (Simaroubaceae). Methods: The gastroprotective effect of ethylacetate fraction of the Hannoa klaineana (50, 100 and 200mg/kg b.wt) was evaluated using aspirin and histamine induced ulcer models. Results: In aspirin-induced ulcer model, the ethylacetate fraction of the Hannoa klaineana demonstrated significant (p<0.001) decreased in mean ulcer index with the maximum protective effect (99.84%) at 200 mg/kg against the gastric damages. While histamine-induced ulcer model, the solvent fraction significantly (p<0.001) decreased mean ulcer index with the protective effect up to 99.83% against the gastric lesions. In both models, a significant (p<0.001) increased in pH value coupled with significant (p<0.001) decreased in gastric volume, free and total acidity in rats pre-treated with varying doses of the ethylacetate fraction was found. Conclusion: The mechanism of gastroprotective effects of ethylacetate fraction of the Hannoa klaineana could be attributed to its ability to stimulate prostaglandins secretion or possess prostaglandins like-substances or suppression of histamine-induced vasospastic effect and gastric secretion. Â Â Â